METHODOLOGICAL REQUIREMENTS FOR IMPROVING TEACHING OF THE DEPARTMENT OF ELECTROMAGNETISM IN HIGHER EDUCATION INSTITUTIONS - Ismailov Batir Berdiyarovish (International Scientific and Current Research Conferences, 2023)
In the article, the main process and phenomena of the electromagnetism department in physics are described in a systematic and structured way.